Expected gains with selection from the simultaneous selection of different quantitative traits in progenies of Eucalyptus camaldulensis DEHNH - de Medeiros Silva, William [UNESP] (2019)
This study aimed to compare the gains obtained with three selection indices and direct and indirect selection applied to the individual genetic values in progeny tests of E. camaldulensis, at the age of six; for shape of stem, diameter at chest height and total height of the trees. The tests were implanted in a randomized complete block design, with 133 progenies and 3.0 m x 1.8 m spacing. Trial 1 (EXP 1) was composed of experimental plots of 5 plants and four replications and in Trial 2 (EXP 2) single tree plot and 20 replicates were used. Estimates of variance components and genetic parameters were obtained using the REML/BLUP method. Selection of individuals was performed based on the individual additive genetic values, through direct and indirect selection of characters and in parallel through the indices of selection of the sum of ranks, expected genetic gains and the sum of Z. The selection indices, in comparison to direct and indirect selection, provide more balanced gains. The index of the sum of ranks and index Z were those that provided greater genetic gains with simultaneous selection in EXP1 (12,74%) and EXP 2 (20,82%), respectively. The selection index Z and sum of ranks were those that presented the most similar results among the selection methods tested in the individual selection by the additive genetic value. EXP 2, because it presents higher values for estimated heritability, provided greater gains with selection.